2017
DOI: 10.1371/journal.pone.0172843
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of the possible role of Acanthamoeba polyphaga in the infection and disease progression in Buruli Ulcer (BU) using ICR mice

Abstract: The transmission of Buruli ulcer (BU), caused by Mycobacterium ulcerans (MU), remains puzzling although a number of hypothesis including through bites of infected aquatic insects have been proposed. We report the results of experiments using ICR mice that give credence to our hypothesis that Acanthamoeba species may play a role in BU transmission. We cocultured MU N2 and MU 1615 which expresses red fluorescent protein (RFP) and Acanthamoeba polyphaga (AP), and confirmed infected AP by Ziehl-Neelsen (ZN) staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Although there is limited experimental data showing that long-term protozoan grazing results in genotypic changes, it has been reported that protozoa can induce the expression of bacterial virulence in the short term, probably due mainly to changes in gene expression. For example, Mycobacterium ulcerans when co-cultured with A. polyphaga infected the footpads of mice much faster than the M. ulcerans only controls ( Azumah et al, 2017 ). S. enterica serotype Typhimurium was shown to enter a hyperinvasive state after passage through A. castellanii ( Carlson et al, 2007 ), and intracellular growth in A. castellanii also induced the invasion and virulence of L. pneumophila in mouse infection models ( Cirillo et al, 1999 ).…”
Section: Predation By Heterotrophic Protists Impacts Pathogens In Envmentioning
confidence: 99%
“…Although there is limited experimental data showing that long-term protozoan grazing results in genotypic changes, it has been reported that protozoa can induce the expression of bacterial virulence in the short term, probably due mainly to changes in gene expression. For example, Mycobacterium ulcerans when co-cultured with A. polyphaga infected the footpads of mice much faster than the M. ulcerans only controls ( Azumah et al, 2017 ). S. enterica serotype Typhimurium was shown to enter a hyperinvasive state after passage through A. castellanii ( Carlson et al, 2007 ), and intracellular growth in A. castellanii also induced the invasion and virulence of L. pneumophila in mouse infection models ( Cirillo et al, 1999 ).…”
Section: Predation By Heterotrophic Protists Impacts Pathogens In Envmentioning
confidence: 99%
“…Although its mode of transmission remains poorly understood [ 4 , 5 , 6 ], studies have shown that it occurs in communities where there are slow flowing rivers, streams and water bodies [ 6 ]. Azumah et al have also demonstrated the involvement of Acanthamoeba in the disease transmission and progression in animal experiments [ 7 , 8 ]. Although the disease occurs elsewhere, the majority of cases are in sub-Saharan Africa where, for example, 1676 of the 1864 new cases of Buruli ulcer worldwide in 2016 were reported from this region [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, S. enterica and L. pneumophila recovered after exposure to A. castellanii display hyperinvasive phenotypes during in vivo infection (Cirillo et al, 1994;Rasmussen et al, 2005). Similarly, mice infections performed with Mycobacterium ulcerans previously co-incubated with A. polyphaga led to enhanced pathogenicity (Azumah et al, 2017). In the case of Vibrio spp., it has recently been shown that their release in EFVs to the extracellular environment results in bacterial growth and colonization advantage in vitro and in vivo, respectively (Espinoza-Vergara et al, 2019).…”
Section: The Impact Of Protozoan Predation On Virulencementioning
confidence: 99%